PENGARUH MEDIA LATIHAN TERHADAP KEMAMPUAN DRIBBLING SEPAK BOLA - Ihsan, Fadli; Atiq, Ahmad; Samodra, Y Touvan Juni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to improve the ability of dribbling in football extracurricular students.The problems that occur in the first dribbling field always widen. Second, touch the foot on the ball too far. The three eyes always go down. Fourth, the position of the body is not parallel when dribbling the ball. Fifth, speed in dribbling is still lacking. Students perform techniques in their own style, do not follow the instructions of the trainer and students feel bored with the training methods not yet using tools to improve their dribbling skills. This problem results in a lack of students' dribbling skills. The form of research used was an experiment using an exercise media audio visual video games training dribbling. The research subjects were 20 participants from Aliya Negeri 1 Pontianak Madrasah 1 Pontianak soccer extracurricular participants. The results of the pretest and posttest dribbling ability are soccer participants in the pretest (68.4), while the posttest is (79.25) and the accumulation of both is the average (79.25) the lowest value (54) the highest value (100) the Standard Deviation (10.20). Data Normality Test Results with the Sig preetest values declared normal. Results Homogeneity of data is declared homogeneous. T Test results are 0.05> 0.00 then Ho is rejected. Based on the results of hypothesis testing, normality test, homogeneity test and discussion, it was concluded that the application of dribbling video games training media had a significant effect on improving soccer dribbling techniques.Keywords: Media, Training, Football and Dribbling Skills.AbstractThis study aims to improve the ability of dribbling in football extracurricular students.The problems that occur in the first dribbling field always widen. Second, touch the foot on the ball too far. The three eyes always go down. Fourth, the position of the body is not parallel when dribbling the ball. Fifth, speed in dribbling is still lacking. Students perform techniques in their own style, do not follow the instructions of the trainer and students feel bored with the training methods not yet using tools to improve their dribbling skills. This problem results in a lack of students' dribbling skills. The form of research used was an experiment using an exercise media audio visual video games training dribbling. The research subjects were 20 participants from Aliya Negeri 1 Pontianak Madrasah 1 Pontianak soccer extracurricular participants. The results of the pretest and posttest dribbling ability are soccer participants in the pretest (68.4), while the posttest is (79.25) and the accumulation of both is the average (79.25) the lowest value (54) the highest value (100) the Standard Deviation (10.20). Data Normality Test Results with the Sig preetest values declared normal. Results Homogeneity of data is declared homogeneous. T Test results are 0.05> 0.00 then Ho is rejected. Based on the results of hypothesis testing, normality test, homogeneity test and discussion, it was concluded that the application of dribbling video games training media had a significant effect on improving soccer dribbling techniquesÂ Keywords: Media, Training, Football and Dribbling Skills.